The Mediating Role of the Principal–Teacher Relationship in Innovative School Leadership and Teacher Professional Learning According to Turkish Teachers’ Perceptions - Mehmet Özdoğru; Yurdagül Doğuş; Muhammet İbrahim Akyürek (Behavioral Sciences)
The relationship between teacher professional learning and school leadership has recently attracted great attention from scientists. However, only a few studies have focused on the relationship between innovative school leadership and teacher professional learning. Therefore, this study aimed to draw attention to the mediating role of the principal–teacher relationship in the relationship between innovative school leadership and teacher professional learning. The study used a quantitative method with a correlational, cross-sectional, and mediation design. Data obtained from 357 teachers working in high schools in Eskişehir, Türkiye, were examined with a mediation analysis based on the bootstrap method. The findings showed that teachers perceived their professional learning highly, school administrators perceived innovative school leadership characteristics highly, and principal–teacher relationships had a significant effect. In addition, moderate positive significant relationships were determined between innovative school leadership and teacher professional learning and principal–teacher relationships; low positive significant relationships were determined between teacher professional learning and principal–teacher relationships. It was determined that the principal–teacher relationship mediated innovative school leadership and teacher professional learning. Our results expand the field’s understanding that innovative leadership is practiced in Türkiye, an eastern society, and that school leadership has the potential to improve student outcomes indirectly through teacher professional learning.